Elit Agama dan Perdamaian: Pertemuan Imam Besar Al-Azhar dan Paus Fransiskus dalam Konstruksi Media - Yanuardanah Yanuardanah; Mualimin Mualimin (Hikmah, 2020)
The focus of this study was to analyze the framing carried out by the Kompas daily towards the meeting of the High Priest of Al-Azhar with Pope Francis in Dubai on 4th of February 2019. The subject of this study was text in the Kompas daily. Meanwhile, the object of study was related to the news framing of the 6th – 7th of February 2019 edition by the printed media of Kompas regarding the meeting of Pope Francis and the High Priest of Al-Azhar. Data were collected through documentation technique. The data obtained were then analyzed through the Zhongdang Pan and Gerald M Kosicki framing analysis models. Based on the analysis of the research data, it was concluded that Kompas framed the meeting of the Catholic Pope and the High Priest of Al-Azhar by emphasizing human aspects. The construction that Kompas wanted to build in its news was related to the importance of openness and dialogue between religious communities. Also, in its news, Kompas framed that coexistence was the main step to achieve peace among people, as to create tolerance among religions and respect for one another. Keywords: Pope Francis, High Priest of Al-Azhar, Media Framing, Kompas Daily